Pengaruh Social Media Marketing, Electronic Word Of Mouth (e-WOM), dan Customer Engagement terhadap Brand Awareness Skincare Glad2Glow pada Generasi Z di TikTok - Mutammima Mutammima; M. Sulhan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research seeks to evaluate how Social Media Marketing, Electronic Word of Mouth (E-WOM), and Customer Engagement affect the Brand Awareness of Glad2Glow skincare products among TikTok users from Generation Z. The rise of digital technology and social media has transformed how consumers behave, particularly Generation Z, who are more inclined to trust online information rather than conventional advertising. TikTok has emerged as a leading platform in Indonesia, with 76% of its users falling within the age group of 18 to 34. The research employs a quantitative methodology with a causal associative framework. Data were gathered through online surveys shared on social media platforms to a sample of 100 participants selected through purposive sampling. The criteria for participants included being between 14 and 29 years old, active TikTok users for at least three months, having viewed Glad2Glow content, and residing in Indonesia. The analysis of the data utilized Structural Equation Modeling-Partial Least Square (SEM-PLS) conducted with SmartPLS 4. 1. The results showed that: (1) Social Media Marketing had no significant effect on Brand Awareness (p-value 0.517 > 0.05); (2) Electronic Word of Mouth had a positive and significant effect on Brand Awareness (p-value 0.015 < 0.05); (3) Customer Engagement had a positive and significant effect on Brand Awareness (p-value 0.000 < 0.05) with the highest path coefficient of 0.537; (4) The three variables simultaneously had a significant effect on Brand Awareness with R-Square value of 0.891, indicating that 89.1% of Brand Awareness variation was explained by the three variables. The findings imply that companies need to prioritize increasing Customer Engagement and effectively managing Electronic Word of Mouth to build Brand Awareness on TikTok platform.